Evaluation of the effects of nicorandil and its molecular precursor (without radical NO) on proliferation and apoptosis of 786-cell - de Paula, Natália Aparecida; Niwa, Andressa Megumi; Vesenick, Diogo Campos; Panis, Carolina; Cecchini, Rubens; de Fátima, Ângelo; Ribeiro, Lúcia Regina [UNESP]; Mantovani, Mário Sérgio (Springer Nature, 2013)
Nicorandil is a nitric oxide (NO) donor used in the treatment of angina symptoms. It has also been reported to protect cells and affect the proliferation and death of cells in some tissues. The molecules that interfere with these processes can cause dysfunction in healthy tissues but can also assist in the therapy of some disorders. In this study we examined the effect of nicorandil and of the molecular precursor that does not have the NO radical (N-(beta-hydroxyethyl) nicotinamide) on the cell proliferation and death of human renal carcinoma cells (786-O) under normal oxygenation conditions. The molecular precursor was used in order to analyze the effects independents of NO. In the cytotoxicity test, nicorandil was shown to be cytotoxic at very high concentrations and it was more cytotoxic than its precursor (cytotoxic at concentrations of 2,000 and 3,000 μg/mL, respectively). We propose that the lower cytotoxicity of the precursor is due to the absence of the NO radical. In this study, the cells exposed to nicorandil showed neither statistically significant changes in cell proliferation nor increases in apoptosis or genotoxicity. The precursor generated similar results to those of nicorandil. We conclude that nicorandil causes no changes in the proliferation or apoptosis of the cell 786-O in normal oxygenation conditions. Moreover, the lack of NO radical in the precursor molecule did not show a different result, except in the cell cytotoxicity. © 2013 Springer Science+Business Media Dordrecht.
Keywords: 786-O cells; Apoptosis; Cell proliferation; Cytotoxicity; N-(beta-hydroxyethyl) nicotinamide; Nicorandil